2015
DOI: 10.1007/s10519-015-9750-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Smoking During Pregnancy and Offspring Birth Weight: A Genetically-Informed Approach Comparing Multiple Raters

Abstract: Maternal smoking during pregnancy (SDP) is a significant public health concern with adverse consequences to the health and well-being of the fetus. There is considerable debate about the best method of assessing SDP, including birth/medical records, timeline follow-back approaches, multiple reporters, and biological verification (e.g., cotinine). This is particularly salient for genetically-informed approaches where it is not always possible or practical to do a prospective study starting during the prenatal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 50 publications
6
51
0
1
Order By: Relevance
“…The current study is also not without some degree of inaccuracy in the MSDP variables, as they are all based on retrospective report. Though it should be noted that in other Missouri twin studies (Heath, Knopik et al 2003; Reich, Todd et al 2003) and Missouri family studies (Knopik et al, current issue) we have observed high reliability and stability of maternal reporting, suggesting that they are likely to be suitable for studying adverse “parent behavior”-“child outcome” associations. Overall, the current study findings may not generalize to other studies utilizing alternative measures of MSDP.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The current study is also not without some degree of inaccuracy in the MSDP variables, as they are all based on retrospective report. Though it should be noted that in other Missouri twin studies (Heath, Knopik et al 2003; Reich, Todd et al 2003) and Missouri family studies (Knopik et al, current issue) we have observed high reliability and stability of maternal reporting, suggesting that they are likely to be suitable for studying adverse “parent behavior”-“child outcome” associations. Overall, the current study findings may not generalize to other studies utilizing alternative measures of MSDP.…”
Section: Discussionmentioning
confidence: 68%
“…Third, our analyses utilized a broad measure of a retrospectively reported maternal smoking during pregnancy. While previous studies support the reliability and utility of retrospective reporting of pregnancy variables by mothers (Heath, Knopik et al 2003; Reich, Todd et al 2003; Christensen, Tobiassen et al 2004; Pickett, Kasza et al 2009; Knopik, Marceau et al ( current issue )), readers should be aware that the sensitivity of the MSDP variable (i.e., its ability to reflect the amount of tobacco exposure by the offspring in utero ) has been shown to be an important factor in the observation of MSDP effects. In an earlier report by Boutwell et al (2011), broadly defined MSDP was not associated with offspring externalizing behavioral problems, however, a continuous measure of MSDP (i.e., the number of cigarette packs smoked per day) was associated with childhood externalizing, such that more packs smoked per day resulted in higher scores on the externalizing problem scale (among matched subjects).…”
Section: Discussionmentioning
confidence: 99%
“…The papers by Knopik et al (2016) and Neiderhiser et al (2016) both address the value of self-report data for assessment of the prenatal environment. In both projects self-report data were collected retrospectively, but other strategies were also used to enhance both the accuracy of the self-report data and the detail of the information collected.…”
Section: Contents Of the Special Issuementioning
confidence: 99%
“…This study also reported that the combined effects of genetic, perinatal, and postnatal risks interact to influence internalizing and externalizing symptoms during early childhood. Knopik et al (2016) focused on identifying the optimal method for assessing smoking during pregnancy (SDP) by comparing rates of agreement across maternal reports, paternal reports of maternal smoking behavior and birth records. These findings support the use of self-report data from mothers and fathers and found a causal association between SDP and birth weight, after controlling for genetic and familial confounds using a sibling comparison approach.…”
Section: Contents Of the Special Issuementioning
confidence: 99%
“…The first paper using MO-MATCH data (Knopik et al, under review) examined rates of agreement across birth record report of SDP, retrospective maternal report of SDP, and retrospective paternal report of SDP. Specifically, we compared reports for any SDP during pregnancy and for quantity of cigarettes smoked across each pregnancy.…”
Section: Retrospective Report Of Sdpmentioning
confidence: 99%